2018
DOI: 10.1007/978-3-030-00919-9_39
|View full text |Cite
|
Sign up to set email alerts
|

End-To-End Alzheimer’s Disease Diagnosis and Biomarker Identification

Abstract: As shown in computer vision, the power of deep learning lies in automatically learning relevant and powerful features for any perdition task, which is made possible through end-to-end architectures. However, deep learning approaches applied for classifying medical images do not adhere to this architecture as they rely on several pre-and post-processing steps. This shortcoming can be explained by the relatively small number of available labeled subjects, the high dimensionality of neuroimaging data, and difficu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 13 publications
3
66
0
1
Order By: Relevance
“…For example, Esmaeilzadeh et al achieved an accuracy of 94.1% using 3D convolutional neural networks to diagnose AD on a dataset with 841 patients. [30] Similar results were obtained by Long et al, who used a support vector machine to diagnose AD based on an MRI scan dataset (n = 427 patients; mean best accuracy = 96.5%) [31] and Zhang et al, who used MRI scans, FDG-PET scans, and CSF biomarkers to diagnose AD (n = 202 patients; AD vs. NL accuracy = 93.2%, MCI vs. NL accuracy = 76.4%). [32] However, the focus of these earlier studies was to use current medical data to diagnose a patient's present cognitive state, in effect demonstrating that a computer can replicate a doctor's clinical decision-making.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…For example, Esmaeilzadeh et al achieved an accuracy of 94.1% using 3D convolutional neural networks to diagnose AD on a dataset with 841 patients. [30] Similar results were obtained by Long et al, who used a support vector machine to diagnose AD based on an MRI scan dataset (n = 427 patients; mean best accuracy = 96.5%) [31] and Zhang et al, who used MRI scans, FDG-PET scans, and CSF biomarkers to diagnose AD (n = 202 patients; AD vs. NL accuracy = 93.2%, MCI vs. NL accuracy = 76.4%). [32] However, the focus of these earlier studies was to use current medical data to diagnose a patient's present cognitive state, in effect demonstrating that a computer can replicate a doctor's clinical decision-making.…”
Section: Introductionsupporting
confidence: 70%
“…Previous work published by others has shown that machine learning algorithms can accurately classify a patient's current cognitive state (normal, MCI, or dementia) using contemporaneous clinical data. [30][31][32] This project has extended this previous work by looking at how past and present clinical data can be used to predict a patient's future cognitive state and by developing machine learning models that can correlate clinical data obtained from patients at one time point with the progression of AD in the future. Several of the machine-learning models used in this project were effective at predicting the progression of AD, both in cognitively normal patients and patients suffering from MCI.…”
Section: Resultsmentioning
confidence: 99%
“…The development of deep-learning technologies in medicine is advancing rapidly [1]. Leveraging labeled big data and enhanced computational power, deep convolutional neural networks have been applied in many neuroscience studies to accurately classify patients with brain diseases from normal controls based on their MR images [1,2]. State-of-the-art saliency visualization techniques are used to interpret the trained model and to visualize specific brain regions that significantly contribute to the classification [2].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we occlude a volumetric patch which is shifted over the entire MRI volume. Although the occlusion method results commonly in much coarser heatmaps (depending on the size of the patch), we included this method because it has been used several times in MRI-based AD classification [7,8,9,12].…”
Section: Methodsmentioning
confidence: 99%